Differential gene expression as a tool to sort individual life stages of a mammalian parasite Trypanosoma brucei - Kunzová, Michaela (Jihočeská univerzita, 2018)
This master thesis aimed to develop a system to sort individual life cycle stages of the mammalian parasite Trypanosoma brucei generated in vitro. T. brucei cell lines expressing developmentally regulatable fluorescent protein due to the stage specific 3'UTRs were generated. Furthermore, a double knock-out of a protein (TbIF1) presumably involved in the parasite's differentiation was attempted.
Differential gene expression as a tool to sort individual life stages of a mammalian parasite Trypanosoma brucei